Os sete níveis de Jacques Lecoq: um estudo performativo e conceitual - Nailanita Prette (2021)
This dissertation had as object of research the Seven Levels of Jacques Lecoq, elaborated by him in the 1980s and, as objective, to present its conceptual basis, sources and references used in the proposition of these tensions scales. Another objective was to understand how the Seven Levels can be upgraded to its application today, and can also assist or be material for creation and body preparation in the arts of the scene. The research methodologies used were performative research and genetic (qualitative) criticism. The first was a reference for the realization of the scenic practice part of the research carried out in the first year of work, in which we researched the Seven Levels as a process of creation and body preparation. Genetic criticism was addressed in the second year and helped us to develop the conceptual part of the work, reconstructing the path of creation and experimentation of the Seven Levels by Jacques Lecoq. As a result, we found that the Seven Levels compose a scenic technical work that enhances the body preparation of the professional of the arts of the scene, because it works the body in its different tensions through improvisation, and can promote a physical preparation combined with creativity. As a creation process, we also achieved the expected results creating a performance that had as narrative the body in its different tensions and that was made based on the exercises of the Seven Levels. Finally, an updated conceptualization of the Seven Levels was elaborated, presenting proposals of nomenclatures for each of them in order to facilitate the communication and pedagogical didactic guidance of this practice, as well as the discussions about this proposal of body work.